2022
DOI: 10.3390/su142114147
|View full text |Cite
|
Sign up to set email alerts
|

Governance and Institutional Drivers of Ecological Degradation in Urban River Ecosystems: Insights from Case Studies in African Cities

Abstract: The degradation of rivers in urban landscapes is alarming and impaired their ecological functions and the services they provide to society. In African cities, urban rivers are among the most degraded ecosystems, yet ecologically sustainable utilisation of river resources can contribute to and support sustainable urban development. In this paper, we identify and analyse key governance and institutional drivers of ecological change in urban river systems in the Swartkops catchment in South Africa and the Federal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The involvement of the local community is essential for the integrated and sustainable river management [58,59,60]. Furthermore, the efforts of the local community should also be supported by the government with clear regulation and assistance as ambiguity in roles, responsibilities, and poor accountability in water governance can lead to poor ecological conditions of rivers [36].…”
Section: Issues Related To Water Utilization and River Ecosystem Serv...mentioning
confidence: 99%
“…The involvement of the local community is essential for the integrated and sustainable river management [58,59,60]. Furthermore, the efforts of the local community should also be supported by the government with clear regulation and assistance as ambiguity in roles, responsibilities, and poor accountability in water governance can lead to poor ecological conditions of rivers [36].…”
Section: Issues Related To Water Utilization and River Ecosystem Serv...mentioning
confidence: 99%
“…Recent studies on the so-called urban river syndrome have shown that the hydrology, ecology, biodiversity, water quality and geomorphology of urban rivers have been severely altered due to pollution, land cover change, poorly designed and over-burden sanitation services, run-off from roads and rail networks, industrial and domestic waste discharges (Capps et al 2016;Jackson et al 2016;Odume 2017). Systemic governance failure and urban poverty have also been identi ed as critical contributors to river ecological degradation in cities (Odume et al 2022). As in many other parts of the world, the implications are that rivers in many cities in Africa have become seriously degraded, compromising their ecological function and the services they provide to society (Capps et al 2016;Chen et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Slow economic recovery: There are also those who are worried about how to recover the economy damaged by the pandemic, which can add stress and feelings of insecurity (Filho et al, 2020). The Nigerian government and non-governmental organizations need to work together to address this mental health problem by providing financial support and mental health services that are readily available and accessible (Odume et al, 2022a). There is also a need to pay attention to spreading knowledge about how to address mental health, as well as increasing the accessibility of mental health services widely throughout the country (Odume et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…The Nigerian government and non-governmental organizations need to work together to address this mental health problem by providing financial support and mental health services that are readily available and accessible (Odume et al, 2022a). There is also a need to pay attention to spreading knowledge about how to address mental health, as well as increasing the accessibility of mental health services widely throughout the country (Odume et al, 2022b). Mental health is an important aspect of public health, and the COVID-19 pandemic has had a significant impact on the mental health of people around the world, including in Nigeria (Giorgi et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%